2020
DOI: 10.2478/jccm-2020-0018
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Pistacia Lentiscus Chia Resin versus Omeprazole in Protecting Male Rats Peptic Mucosa against Cold Restraint Stress

Abstract: IntroductionPeptic mucosal damage induced by acute stress is a serious cause of morbidity and mortality in critically ill patients. The study aimed to investigate the protective, antioxidant and anti-inflammatory effects of pretreatment with Chios mastic gum (CMG), a traditionally consumed herbal resin naturally deriving from the trunk of Pistacia Lentiscus var. Chia compared to Omeprazole, a standard medication used in the prevention and treatment of gastritis, against the effects of cold restraint stress (CR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
2
0
5
Order By: Relevance
“…More interestingly, the biological actions of Chios Mastiha have driven the attention of many research groups in recent years. A wide variety of anti-microbial [ 3 , 32 , 33 , 34 ], anti-oxidant [ 4 , 35 , 36 ], anti-inflammatory [ 9 , 37 , 38 , 39 ], anti-hyperlipidemic [ 40 , 41 , 42 , 43 ], anti-hyperglycemic [ 41 , 44 ], and anti-cancer [ 45 , 46 , 47 ] actions have emerged through in vitro and in vivo experiments, and through clinical trials, too. These biological actions are proposed to be attributed to Chios Mastiha bioactive substances, such as triterpenes [ 3 , 6 , 7 , 8 , 48 ], β-myrcene [ 1 ], phenolics [ 9 ], arabino-galactan proteins, neutral sugars, and uronic acids [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More interestingly, the biological actions of Chios Mastiha have driven the attention of many research groups in recent years. A wide variety of anti-microbial [ 3 , 32 , 33 , 34 ], anti-oxidant [ 4 , 35 , 36 ], anti-inflammatory [ 9 , 37 , 38 , 39 ], anti-hyperlipidemic [ 40 , 41 , 42 , 43 ], anti-hyperglycemic [ 41 , 44 ], and anti-cancer [ 45 , 46 , 47 ] actions have emerged through in vitro and in vivo experiments, and through clinical trials, too. These biological actions are proposed to be attributed to Chios Mastiha bioactive substances, such as triterpenes [ 3 , 6 , 7 , 8 , 48 ], β-myrcene [ 1 ], phenolics [ 9 ], arabino-galactan proteins, neutral sugars, and uronic acids [ 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anti-inflammatory activity of the whole extract from Chios Mastiha powder has been previously reported. Thus, it has been observed that Chios Mastiha powder reduced the serum TNFα levels in male rats with gastric mucosal inflammation [ 38 ]. Moreover, it has been shown that Chios Mastiha neutral extract suppressed the phosphorylation of p65 subunit of NF-κΒ in TNFα-stimulated human aortic endothelial cells (HAEC) [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…A gastrite é uma patologia definida por alterações histológicas no revestimento do estômago, onde se observa infiltrado de células inflamatórias (Silva, et al, 2018). Lesões da mucosa gástrica podem ser focal ou difusa, superficial ou potencialmente resultando em ulceração ou hemorragia gástrica, que está associada à significativa morbidade e mortalidade (Kakagia, et al, 2020). De distribuição universal, a gastrite é prevalente em cerca de 50% da população mundial (Ddine, et al, 2020).…”
Section: Discussionunclassified
“…Os principais sintomas são representados por dor epigástrica, pirose, náuseas, vômitos, sensação de saciedade precoce e desconforto abdominal (Barbosa, et al, 2010). O Omeprazol tem sido utilizado como medicamento padrão no tratamento de danos gástricos e na prevenção de úlcera péptica desde 1989, entretanto tem sido associado a efeitos adversos e interações medicamentosas (Kakagia, et al, 2020).…”
Section: Discussionunclassified
“…Ακόμη, μειωμένα κατά 34,6% και 63,9% ήταν και τα επίπεδα του TNFα και της ιντερλευκίνης 1β (IL-1β), αντίστοιχα. Στα ζώα που τους χορηγήθηκε παράλληλα με τη Μαστίχα και ομεπραζόλη, η Μαστίχα μείωσε κατά 45,7% περισσότερο από την ομεπραζόλη τα επίπεδα του TNFα και κατά 19% περισσότερο τα επίπεδα της IL-1β [58].…”
Section: αντιφλεγμονώδεις δράσειςunclassified